Depression and death anxiety among patients undergoing hemodialysis during the COVID-19 pandemic in Palestine: a cross sectional study - Ibrahim, Mohammed; Saeed, Elias; Hamarsheh, Islam; Al Zabadi, Hamzeh; Ahmead, Muna (Frontiers in Psychiatry, 2023)
Patients undergoing dialysis are vulnerable to serious complications like extended hospital stays and psychosocial issues like depression and death anxiety. The effects of psychosocial factors on end-stage renal disease patients' outcomes during the COVID-19 pandemic are not taken into account enough.During the COVID-19 pandemic, the study sought to determine the prevalence of depression and death anxiety among Palestinian hemodialysis patients and the relationship between sociodemographic and clinical characteristics.A convenience sampling technique was used to select 308 hemodialysis patients from five hemodialysis units located in government hospitals in Palestine for the cross-sectional study. Beck Depression Inventory and the Templers Death Anxiety Scale were used to collect data, which was then analyzed using SPSS version 20.Nearly 66.2% of the sample had depression symptoms, 61.4% met the diagnostic threshold for depression, and 69.8% had death anxiety. Further, the multivariate analysis revealed that having a female identity, residing in a city or refugee camp, and patients who reported not experiencing depression had a significant relationship with death anxiety, while having a higher educational level than 12 years, having one or more chronic co-morbidities, and patients who reported experiencing death anxiety had a significant correlation with depression.According to the results of our study, patients receiving hemodialysis frequently experience depression and death anxiety. Because of this, these patients should receive a psychiatric evaluation in the early stages of their illness so that timely and appropriate psychological interventions can be given in hemodialysis facilities in Palestine.